2016
DOI: 10.1007/s11418-015-0952-2
|View full text |Cite
|
Sign up to set email alerts
|

Longgu (Fossilia Ossis Mastodi) alters the profiles of organic and inorganic components in Keishikaryukotsuboreito

Abstract: Longgu (Fossilia Ossis Mastodi) is a non-botanical crude drug, defined as "the ossified bone of large mammal" in the Japanese Pharmacopoeia sixteenth edition (JP16). It is a non-reproducible drug and is now facing the threat of exhaustion. To solve this problem, we aimed to clarify the role of longgu in Kampo prescriptions, which has not yet been scientifically ascertained. In this study, we focused on decoction of Keishikaryukotsuboreito (KRB). The profile of inorganic and organic components in the extract wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In previous studies, orally administrated longgu powder and 80% methanol extract have shown sedative effects in rats and mice. 3,4) However, longgu is a component of Kampo formulas and their decoctions or extracts are generally used in clinical practice. Therefore, patients rarely take longgu powder and methanol extracts of longgu.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, orally administrated longgu powder and 80% methanol extract have shown sedative effects in rats and mice. 3,4) However, longgu is a component of Kampo formulas and their decoctions or extracts are generally used in clinical practice. Therefore, patients rarely take longgu powder and methanol extracts of longgu.…”
Section: Introductionmentioning
confidence: 99%